Manajemen Keuangan Sebagai Jantung Perusahaan Dalam Meningkatkan Daya Saing - Yuli Angraini (Sammajiva: Jurnal Penelitian Bisnis dan Manajemen, 2026)
Financial management plays a crucial role in the sustainability and development of a company. In increasingly competitive business environments, companies are required to have the right financial management strategies to increase their competitiveness. This article aims to analyze the role of financial management as the core or "heart" of a company in supporting competitive advantage. The method used is a literature review from various scientific sources. The results of the discussion indicate that effective financial management can improve operational efficiency, optimize resource utilization, and support appropriate strategic decision-making. Thus, financial management contributes significantly to increasing a company's competitiveness in the market.